POLITICAL AND ECONOMIC INTEGRATION PROCESSES IN CENTRAL ASIAN STATES: ACHIEVEMENTS AND OBSTACLES - Xudoyberdiyev Otabek Zafar o'g'li (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Annotation: This article explores the political and economic integration efforts among Central Asian countries since their independence in the early 1990s. It analyzes the progress made toward regional cooperation in trade, infrastructure, energy, and security, with particular emphasis on multilateral platforms such as the Central Asia Regional Economic Cooperation (CAREC) Program and the recent regional summits initiated by Uzbekistan. The paper also discusses the internal and external challenges that hinder deeper integration, including political differences, border disputes, competition for resources, and the influence of global powers. Ultimately, the article evaluates whether sustainable regional integration in Central Asia is achievable and what steps are necessary to overcome the existing barriers.